2016
DOI: 10.1016/j.msec.2015.09.055
|View full text |Cite
|
Sign up to set email alerts
|

Effect of bimodal harmonic structure design on the deformation behaviour and mechanical properties of Co-Cr-Mo alloy

Abstract: In the present work, Co-Cr-Mo alloy compacts with a unique bimodal microstructural design, harmonic structure design, were successfully prepared via a powder metallurgy route consisting of controlled mechanical milling of pre-alloyed powders followed by spark plasma sintering. The harmonic structured Co-Cr-Mo alloy with bimodal grain size distribution exhibited relatively higher strength together with higher ductility as compared to the coarse-grained specimens. The harmonic Co-Cr-Mo alloy exhibited a very com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
38
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 72 publications
(39 citation statements)
references
References 42 publications
0
38
1
Order By: Relevance
“…Vickers hardness of CCM HPT processed at ε eq = 9 (N = 1) at half radius (~521 HV) is greater than those of ne-grained (~480 HV) and coarse-grained (~440 HV) regions of bimodal structured CCM alloy. The greater hardness obtained in CCM HPT processed at ε eq = 9 (N = 1) is attributed to its smaller grain diameter and higher volume fraction of the ε phase (the volume fraction of the ε phase is around 20% for bimodal structured CCM alloy) 54) . In addition, the hardness of CCM HPT processed at ε eq = 9 (N = 1) almost does not differ with increasing distance from the center of the specimen, r (2, 3, and 5 mm), which may be because of the achieved microstructural homogeneity.…”
Section: Microstructural Evolutionmentioning
confidence: 97%
See 1 more Smart Citation
“…Vickers hardness of CCM HPT processed at ε eq = 9 (N = 1) at half radius (~521 HV) is greater than those of ne-grained (~480 HV) and coarse-grained (~440 HV) regions of bimodal structured CCM alloy. The greater hardness obtained in CCM HPT processed at ε eq = 9 (N = 1) is attributed to its smaller grain diameter and higher volume fraction of the ε phase (the volume fraction of the ε phase is around 20% for bimodal structured CCM alloy) 54) . In addition, the hardness of CCM HPT processed at ε eq = 9 (N = 1) almost does not differ with increasing distance from the center of the specimen, r (2, 3, and 5 mm), which may be because of the achieved microstructural homogeneity.…”
Section: Microstructural Evolutionmentioning
confidence: 97%
“…In addition, the UTS of CCM HPT processed at ε eq = 2.25 is also greater than that of bimodal structured CCM alloy (~1300 MPa) 53) . Abovementioned phenomenon is attributed to that the average grain diameter of CCM HPT processed at ε eq = 2.25 in nanometerscale (~84 nm) is smaller than that of CCM HF (~0.8 µm) 53) and bimodal structured CCM alloy consisting of ne-grained and coarse-grained regions, which has an average grain diameter around 2-5 µm in ne-grained region and 36.8 µm in coarse-grained region 54) . The UTS of CCM HPT was still high but decreases slightly at ε eq = 18 in comparison to those at ε eq = 2.25 and 9, and it subsequently saturated at ε eq > 18.…”
Section: Microstructural Evolutionmentioning
confidence: 99%
“…Considering the improved ductility in harmonic structured material, in earlier works, 9,14) it has been experimentally demonstrated that an improvement in the ductility is attributed to the large uniform deformation under tensile loading. In other words, strain hardening is kept to larger strain region, and thus resulting in the improvement of ductility.…”
Section: Introductionmentioning
confidence: 99%
“…The effect of topological distribution of fine-and coarse areas on the properties was also evaluated wherein random bimodal was created by mixing severely milled powders with un-milled initial powders. [19,24,25] It was observed that the random bimodal structured specimens demonstrated higher strengths when compared to bulk CG specimens. Moreover, other important observations were also made from these studies: (a) Both random and HS bimodal exhibit same strength but HS exhibit higher ductility when compared to random bimodal; (b) the HS specimens show extremely small variation of properties when compared to random bimodal specimens.…”
mentioning
confidence: 99%
“…To deal with the above-mentioned issues of controlled heterogeneous microstructure, Ameyama et al proposed an integrated approach to prepare bulk materials with a controlled and unique heterogeneous microstructure, called 'harmonic structure' (HS), with bimodal grain size distribution. [15][16][17][18][19][20][21][22][23][24][25] A schematic diagram illustrating the HS design is shown in Figure 1. The HS is a heterogeneous microstructure with a specific spatial distribution of fine and coarse grains, that is, the CG areas ('core') embedded in the matrix of three-dimensional continuously connected network ('shell') of fine-grained (FG) areas.…”
mentioning
confidence: 99%